2019
DOI: 10.3389/fneur.2019.01190
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Risk Factors for the Recurrence of Benign Paroxysmal Positional Vertigo

Abstract: Benign paroxysmal positional vertigo (BPPV) manifests itself as a paroxysm of vertigo and nystagmus lasting several seconds, which is self-limiting. The clinical characteristics and risk factors for the recurrence of BPPV in different ages have not yet been investigated.Materials and Methods: A retrospective observational study was conducted in the Department of Neurology in Beijing Tiantan Hospital from July 2009 to June 2015. The study included 1,012 patients aged 18–93 years. All patients received the defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 32 publications
3
47
0
1
Order By: Relevance
“…Some studies have investigated associations between vascular risk factors and BPPV, such as hypertension, DM, and hyperlipidemia, but the results were controversial (4,19). In addition, vascular comorbidities may also be risk factors for BPPV recurrence (8,9). However, our analysis showed that migraine and high TC level were risk factors for BPPV occurrence, while HTN, DM, hyperlipidemia, and stroke were not.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Some studies have investigated associations between vascular risk factors and BPPV, such as hypertension, DM, and hyperlipidemia, but the results were controversial (4,19). In addition, vascular comorbidities may also be risk factors for BPPV recurrence (8,9). However, our analysis showed that migraine and high TC level were risk factors for BPPV occurrence, while HTN, DM, hyperlipidemia, and stroke were not.…”
Section: Discussionmentioning
confidence: 62%
“…This relationship may be related to estrogen deficiency in postmenopausal women, as estrogen may promote the development of osteoporosis and even BPPV (18). In addition, women BPPV patients have a higher risk of recurrence than men (9,31). Therefore, further research between estrogen levels and BPPV may help early diagnosis and prevention of BPPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morbidity of BPPV in male and female is 1:1.5-2, which is usually high after 40 years old and increases with age (4). In addition, some studies have found that age does not increase the recurrence rate of BPPV (10).We found the recurrence of females was 3.79 fold which signi cantly higher than male but the female -to-male ratio was 1.82 to 1 in total patients. In theory, with the increase of age, the function of human organs gradually decline.…”
Section: Discussionmentioning
confidence: 40%
“…As we all know, age, gender, sex hormones, osteoporosis, hypertension, hyperlipidemia, diabetes and hyperuricemia are all considered as risk factors of BPPV (6)(7)(8)(9). According to previous study that cerebrovascular risk factors in uenced BPPV recurrence (10). The morbidity of BPPV in male and female is 1:1.5-2, which is usually high after 40 years old and increases with age (4).…”
Section: Discussionmentioning
confidence: 99%